(untitled) - Wells, David J. (New York, 1995)
This book will help you better understand why leaving school and going to work is often difficult, and what you can do to avoid the many common obstacles to career growth and satisfaction. It will also help you to understand important perceptual differences that occur between new hires and management and how to overcome the communication problems that can result. An increased abiity to meet your employer's needs as well as your own is the value-added you.
Keywords: Engineering,Career development,Kỹ thuật,Phát triển nghề nghiệp; Vocational guidance,Hướng nghiệp